2017
DOI: 10.1038/cddis.2017.83
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA BLACAT1 indicates a poor prognosis of colorectal cancer and affects cell proliferation by epigenetically silencing of p15

Abstract: Recently, a novel class of transcripts, long noncoding RNAs (lncRNAs), is being identified at a rapid pace. These RNAs have critical roles in diverse biological processes, including tumorigenesis. One of them, BLACAT1, a cancer-associated long noncoding RNA, exerts regulatory functions in various biological processes in cancer cells, however, the role of BLACAT1 in colon cancer remains unclear. Our experiments showed that increased BLACAT1 was an independent unfavorable prognostic indicator for colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 32 publications
4
79
0
Order By: Relevance
“…P15 and P16 have also been identified as tumor-suppressive proteins in CRC [49, 51]. In this study, we reported that overexpression of P57 and KLF2 can inhibit proliferative ability of CRC cells, and cause G1/G0 phase arrest.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…P15 and P16 have also been identified as tumor-suppressive proteins in CRC [49, 51]. In this study, we reported that overexpression of P57 and KLF2 can inhibit proliferative ability of CRC cells, and cause G1/G0 phase arrest.…”
Section: Discussionmentioning
confidence: 60%
“…We also reported that lncRNA HOXA-AS2 mediated CRC proliferation partly through inhibiting P21 and KLF2 expression [30]. In addition, the effects of P15 and P16 on CRC progression have been studied previously [49-51]. …”
Section: Resultsmentioning
confidence: 99%
“…Pei et al (15) reported that downregulation of lncRNA CASC2 promoted cell proliferation and metastasis of bladder cancer by activating the Wnt/Ī²-catenin signaling pathway. And also many lncRNAs, for instance, ROR, BLACAT1, ANCR, TUG1, are identified to be dysregulated and play critical role in the initial and progression of CRC (14,(16)(17)(18). FAM83H-AS1 has been identified to play critical roles in lung cancer and breast cancer (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xia et al (13) demonstrated that long noncoding RNA papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3) inhibited proliferation and invasion of glioma cells by suppressing the Wnt/Ī²-catenin signaling pathway. Su et al (14) illustrated that long noncoding RNA BLACAT1 indicated a poor prognosis of colorectal cancer and affected cell proliferation by epigenetically silencing p15. Pei et al (15) reported that downregulation of lncRNA CASC2 promoted cell proliferation and metastasis of bladder cancer by activating the Wnt/Ī²-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, long non-coding RNAs (lncRNAs), newly identified members of the noncoding RNA family with length >200 nucleotides (nt), have been proposed (2)(3)(4). Accumulating documents have revealed that lncRNAs play a critical role in tumorigenesis and can be used as biomarkers for diagnosis or prediction of survival and recurrence in multiple cancers (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%